On the development and use of improved methodologies for irrigation management - Lenton, R. (1986)
The paper is concerned with the development and use of general approaches for irrigation management that are not specific to any irrigation system and can be applied in a broad range of situations. It attempts to (1) clarify the concept of an irrigation management methodology; (2) examine to what extent methodologies are available and used in practice in the management of irrigation systems around the world; and (3) explore research needs and draw lessons which may be employed in the development of improved methodologies. The focus of the paper is on large-scale, publicly administered irrigation systems such as those prevalent in much of South and Southeast Asia.